PERBEDAAN SIKAP RESPECT DITINJAU DARI JENIS KELAMIN - Puguh Ari Fatchurrohman (Counseling Milenial (CM), 2024)
Respect can be interpreted as appreciating or respecting. In general, respect is a way of feeling and behaving. In the world of education, respect is associated with the relationship between students and teachers. Each student must have an attitude of respect that must be grown in each of them. The purpose of this study was to determine the attitude of respect in class VIII students at SMPN 37 Semarang. This research is a quantitative research using survey research methods and the type of research is descriptive. The sampling technique used in this study is simple random sampling with the population in this study amounting to 216 students while the sample in this study amounted to 179 students. The results of the research that has been carried out are that the percentage of respect for students in class VIII SMPN 37 Semarang is dominant at a high level, which is 73% with a total of 131 out of 179 students and at a very high level, which is 17% with a total of 31 out of 179 students, so it can be concluded that the level of respect for the class VIII students of SMPN 37 Semarang is relatively high.